Hollow maxillary denture: A new modified technique for improving retention in resorbed maxillary ridges - Laxman Singh Kaira; Esha Dabral (SRM Journal of Research in Dental Sciences, 2014)
The success of a complete denture relies on the principles of retention, stability, and support. The prosthodontist skill lies in applying these principles efficiently in critical situations. Severely resorbed maxillary edentulous ridges that are narrow and constricted with increased interridge space provide decreased support, retention, and stability. The consequent weight of the processed denture only compromises them further. This article describes a case report of an edentulous patient with resorbed ridges, where a simplified technique of fabricating a hollow maxillary complete denture was used for preservation of denture bearing areas.